The Trend of Permeability of Loess in Yili, China, under Freeze–Thaw Cycles and Its Microscopic Mechanism - Qianli Lv (MDPI AG, 2021)
Loess landslides induced by the freeze–thaw effect frequently occur in Yili, China. Freeze–thaw cycles cause indelible changes in the soil microstructure, affecting its permeability. This study investigated the impacts of freeze–thaw cycles on the permeability of Yili loess using permeability tests on undisturbed (virgin, in situ) and remolded loess samples taken before and after freeze–thaw cycles. Scanning electron microscopy and nuclear magnetic resonance techniques were utilized to investigate the microscopic mechanism of the freeze–thaw process on the loess. Grey relation analysis (GRA) was employed to analyze the correlation between macroscopic permeability and microscopic parameters (maxi. radius, eccentricity, fractal dimension, directional probability entropy, and porosity). The results revealed that the permeability and all the microstructure parameters have roughly shown the same trend: “fluctuation–towards equilibrium–stability”. Firstly, the permeability coefficients of original and remolded loess experienced three and two peaked–trends, respectively, before 30 freeze–thaw cycles. The trends eventually stabilized within 30–60 freeze–thaw cycles. Increased number of freeze–thaw cycles disintegrated large particles in undisturbed loess into medium–sized particles, and particle shapes became more uncomplicated. Medium–sized particles in the remolded loess agglomerated to larger particles with more complex shapes. Furthermore, the overall porosity of the originally undisturbed loess decreased, and large and medium–sized pores transformed into small pores and micropores. In contrast, the overall porosity of remolded loess increased. Finally, the results revealed that permeability coefficients of the undisturbed and remolded loess became closely related with eccentricity and porosity, respectively. This study provides a reference for preventing and governing the loess landslides induced by the freeze–thaw cycles and permeability reduction in construction on loess in seasonally frozen areas in Yili.